Implantation failures: Success of assisted hatching with quarter-laser zona thinning - Petersen, Cláudia G.; Mauri, A. L.; Baruffi, R. L.; Oliveira, J. B A; Massaro, F. C.; Elder, K.; Franco, J. G. [UNESP] (Elsevier, 2005)
Implantation failure after IVF is one of the factors associated with a reduced chance of pregnancy for some patients. Assisted hatching methodologies are designed to facilitate the embryo's escape from the zona pellucida, and this strategy has been suggested as a means of improving pregnancy rates in patients with previous implantation failure. The aim of this prospective and randomized study was to evaluate the efficacy of quarter-laser zona thinning assisted hatching (qLZT-AH) in improving the implantation of embryos in patients with previous implantation failure. A total of 150 patients with a history of previous implantation failure were treated with intracytoplasmic sperm injection, and allocated into two groups: group 1, only one previous implantation failure, and group 2, repeated implantation failures. The patients in each group were randomized at the time of embryo transfer into a control group (no qLZT-AH) or experimental group where qLZT-AH was performed. For patients with repeated implantation failures, the implantation rate in those who received laser-thinned embryos was significantly higher (P=0.02) than in those whose embryos were not laser-thinned (10.9 and 2.6% respectively). However, this difference was not observed in patients who presented with only one previous implantation failure. The data demonstrate that qLZT-AH is an effective strategy for improving the implantation of embryos in patients with repeated implantation failures.
Keywords: Implantation failure; Quarter-laser zona thinning and assisted hatching; nafarelin acetate; recombinant follitropin; adult; clinical trial; controlled clinical trial; controlled study; data analysis; embryo; embryo transfer; experimental design; female; human; infertility therapy; intracytoplasmic sperm injection; laser; major clinical study; male; nidation; pregnancy rate; prospective study; quarter laser zona thinning assisted hatching; randomized controlled trial; statistical significance; treatment failure; treatment planning; zona pellucida; Adult; Embryo Implantation; Embryo Transfer; Female; Fertilization in Vitro; Humans; Infertility; Lasers; Pregnancy; Pregnancy Outcome; Prospective Studies; Sperm Injections, Intracytoplasmic; Zona Pellucida